Blessing the world : ritual and lay piety in medieval religion - Rivard, Derek A. (Catholic University of America Press, 2009)
"In this book, Derek A. Rivard studies liturgical blessing and its role in the religious life of Christians during the central and later Middle Ages, with a particular focus on the blessings of the Franco-Roman liturgical tradition from the tenth to late thirteenth centuries. Through a careful and extensive study of more than ninety such blessings, many of them translated for the first time and accessible to a readership beyond specialists in medieval liturgy, the author argues that medieval blessings were composed as a direct response to the needs, anxieties, beliefs, and fears of the laity, and therefore these texts represent a rich and largely untapped source for the study of lay piety and of ritual in medieval Europe."--Jacket.